Stigmatization of consensual non-monogamous partners: Perceived endorsement of conservation or openness to change values vary according to personal attitudes - Rodrigues, D. L. (2022)
Studies have shown that romantic partners in consensual non-monogamous (CNM) relationships are targets of stigmatization. However, little is known about the underlying mechanisms and the conditions under which such stigmatization occurs. In two experimental studies (combined N = 772), we asked participants to read the description of two partners in a relationship (monogamous vs. open relationship vs. polyamorous) and make a series of judgments about those partners. Overall results showed that CNM (vs. monogamous) partners were perceived as less trustworthy and as having more sexual health concerns (Studies 1 and 2), and as being less committed and less sexually satisfied (Study 2). Results from a conditional mediation analysis (Study 2) further showed that participants with negative attitudes toward consensual non-monogamy perceived CNM (vs. monogamous) partners as having less conservation and more openness to change values, which was then associated with more stigmatization. In contrast, participants with positive attitudes toward consensual non-monogamy perceived CNM (vs. monogamous) partners as having more openness to change values, which was then associated with less stigmatization. Taken together, these results extended the literature focused on prejudice, discrimination, and stigmatization of minority groups and highlighted key elements that can be used to buffer stigmatization.